The Development of Attraction in Natural Tourism Object “Agrowisata Taman Arum” in Sumber Sari Village Loa Kulu Sub-District - Novi Anugraheni; Elin Diyah Syafitri; Devi Triwidya (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2022)
Agrowisata Taman Arum is one of the natural tourism objects in Sumber Sari Village, Loa Kulu Subdistrict. Attractions can develop if they have a tourist attraction where the attraction will encourage tourists to visit a tourist attraction. While natural tourism activities in Sumber Sari Village are hampered to develop because the tourist attraction that is owned by this village has not been well managed by the local community and tourism managers. One of the impacts is a decrease in the number of tourists each year by 52% from 2015 to 2019. Therefore, the purpose of this study is to analyze more deeply related to the natural attractions of Taman Arum Agro Tourism. The research analysis method used is a Likert-descriptive scale. The results obtained include the development of natural resource cultivation ((paddy agriculture and plantations), flora, customs / culture, water), the development of tourism activities (agro-tourism, shopping (picking / harvesting fruits and vegetables), and education), the development of hygiene management and tourism security to minimize problems caused by tourist trash, animals (intruders / destroyers), natural disasters (floods / landslides), disturbance to flora, fires, illegal logging and encroachment.